Non-contact left ventricular endocardial mapping in cardiac resynchronisation therapy. Issue 1 (15th December 2003) - Lambiase, P D; Rinaldi, A; Hauck, J; Mobb, M; Elliott, D; Mohammad, S; Gill, J S; Bucknall, C A
Abstract : Background: Up to 30% of patients with heart failure do not respond to cardiac resynchronisation therapy (CRT). This may reflect placement of the coronary sinus lead in regions of slow conduction despite optimal positioning on current criteria. Objectives: To characterise the effect of CRT on left ventricular activation using non-contact mapping and to examine the electrophysiological factors influencing optimal left ventricular lead placement. Methods and results: 10 patients implanted with biventricular pacemakers were studied. In six, the coronary sinus lead was found to be positioned in a region of slow conduction with an average conduction velocity of 0.4 m/s, v 1.8 m/s in normal regions (p < 0.02). Biventricular pacing with the left ventricle paced 32 ms before the right induced the optimal mean velocity time integral and timing for fusion of depolarisation wavefronts from the right and left ventricular pacing sites. Pacing outside regions of slow conduction decreased left ventricular activation time and increased cardiac output and dP/dtmax significantly. Conclusions: In patients undergoing CRT for heart failure, non-contact mapping can identify regions of slow conduction. Significant haemodynamic improvements can occur when the site of left ventricular pacing is outside these slow conduction areas. Failure of CRT to produce clinical benefits may reflect left ventricular lead placement in regions of slow conduction which can be overcome by pacing in more normally activating regions.